2018
DOI: 10.15171/hpr.2018.20
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction With Hospital Food service and its Impact on Plate Waste in Public Hospitals in East Malaysia

Abstract: Background:Foodservice is an important issue in hospital settings, and patients' levels of satisfaction are often indicated by consumption and plate waste. Objective: The current study compared patient satisfaction in hospital areas and other factors and determined the relationship between patient satisfaction and plate waste. Methods: This quantitative research was performed in four East Malaysian public hospitals. Patients at these hospitals were asked to complete a questionnaire which had three parts: A) ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 39 publications
5
16
0
6
Order By: Relevance
“…This finding disagrees with the result of [30] who disclosed that 75.7% of patients mentioned that the hospital introduced enough food amounts. In addition more than two thirds of hospitalized children or their mothers were reported that the hospital provided food of bad quality, which was similar with another study finding that indicated that patients were scored food quality as the lowest, because there was less variety in the menu [36], which is also compatible with the current study findings (Table 5). This can be explained by the fact that in most Egyptian public hospitals, no menus were distributed; hence, patients do not have choices on what will be served.…”
Section: Discussionsupporting
confidence: 92%
“…This finding disagrees with the result of [30] who disclosed that 75.7% of patients mentioned that the hospital introduced enough food amounts. In addition more than two thirds of hospitalized children or their mothers were reported that the hospital provided food of bad quality, which was similar with another study finding that indicated that patients were scored food quality as the lowest, because there was less variety in the menu [36], which is also compatible with the current study findings (Table 5). This can be explained by the fact that in most Egyptian public hospitals, no menus were distributed; hence, patients do not have choices on what will be served.…”
Section: Discussionsupporting
confidence: 92%
“…Despite that, comparison made between several local studies in Malaysian was varied. A hospital plate waste study carried out by Zakiah et al [ 9 ] among patients on regular diet obtained a comparable rate with overall mean plate waste of 42.6% while a more recent study involving several public hospitals in East Malaysia by Aminuddin et al [ 45 ] reported a slightly lower average plate waste of 36%. However, percentage comparison between the results obtained from this study and other TMD studies could not be made since published works on the rate of TMD plate waste are rare if not none.…”
Section: Discussionmentioning
confidence: 94%
“…Personal satisfaction with the meals served is significantly negatively correlated with tourist FWRE. As an index of foodservice quality, food waste could reflect consumer satisfaction (Aminuddin, Vijayakumaran, & Razak, 2018;Ferreira, Martins, & Rocha, 2013). Satisfaction of meals is also the most intuitive embodiment of whether the food can satisfy tourist appetite and can directly determine whether the food is likely to be wasted.…”
Section: Food Waste Composition and Patterns Of Wasteful Behaviour Among Touristsmentioning
confidence: 99%